Protectors, Aggressors, and Kinfolk: Dogs in a Tribal Community. (4th May 2018) - Jervis, Lori L.; Warren, Diane; Salois, Emily Matt; Ketchum, Scott; Tallbull, Gloria; Spicer, Paul
ABSTRACT: Free-roaming dogs are a common phenomenon on many American Indian reservations as well as globally. Lack of canine restriction may be pathologized by outsiders, assumed to be a "problem" that reflects underlying individual or community dysfunction. Seldom investigated are the cultural logics underlying the lack of restriction, and the positive role that dogs may be playing in the community. This paper examines relationships between a northern plains reservation community and their dogs. We found these relationships to be complex and multifaceted, harkening back to a pre-contact past when human survival itself depended on the dog, and extending into a present shaped by a broad range of cultural notions about the human–dog relationship. We explore the concept of dog restriction, asking what it means for connections with dogs in a context where relationships with dogs run deep, but have been disrupted by settler colonialism. We found a community that very much desires dogs and views them positively, with their role as protector highly valued on nearly every level. While traditional notions guided many behaviors toward dogs, other conceptualizations were simultaneously in play, including rural ideas about animals as well as American popular culture. Our findings call into question the ethnocentric bias that construes all free-roaming dogs as strays, which is linked to cultural notions of "pet ownership" that equate love for dogs with restrictions on their movement.